Effect of health education on birth preparedness and complication readiness on the use of maternal health services: A propensity score-matched analysis - Izudi, Jonathan; Akwang, Denise Grace; McCoy, Sandra I.; Bajunirwe, Francis; Kadengye, Damazo T. (Midwifery, 2019)
Objective: At 789 maternal deaths per 10 0,0 0 0 live births, South Sudan has one of the worst maternal mortality indicators in the world. Utilization of maternal health services namely antenatal care (ANC), skilled birth attendance (SBA), and early postnatal care (EPNC) is critical in reducing these deaths. We evaluated whether health education on birth preparedness and complication readiness (BPCR) has an impact on the utilization of skilled birth attendance and early postnatal care in Mundri East County, South Sudan. Design: We used observational data collected from antenatal clinics in South Sudan to perform a propensity score matched analysis. Treatment effects in both unmatched and matched cohorts were estimated using modified Poisson regression analysis with robust standard errors in prevalence risk ratios (PR) and 95% confidence intervals. Setting: 13 primary healthcare facilities. Participants: 385 postpartum mothers. Interventions: Health education on BPCR. Measurements: Two outcomes were evaluated: (1) SBA measured as delivery in a health facility, and (2) EPNC use measured as use of postnatal care within 2–7 days of delivery. Findings: Data on 243 (67.9%) mothers who attended antenatal care were analyzed. 92 participants who received BPCR health education were matched with 92 who had never. In unmatched adjusted analysis, health education on BPCR significantly increased SBA (Adjusted PR (APR), 1.99; 95% confidence interval (CI), 1.99–3.65) but not EPNC use (APR, 1.78; 95% CI, 0.73–4.35). In propensity score-matched analysis, SBA significantly improved (PR, 2.64; 95% CI, 1.91–3.66) while the increase in EPNC use was insignificant (PR, 1.14; 95% CI, 0.43–3.03). Conclusions: Health education on BPCR improves SBA but not EPNC use among mothers in Mundri East County, South Sudan. Implication for practice: South Sudan’s health systems should design new strategies to enhance EPNC use in order to significantly reduce maternal and newborn deaths in the earlier days of the postpartum period. In addition, a qualitative study is needed to identify barriers to EPNC use.
Keywords: Birth preparedness and complication; Readiness; Postnatal care; Maternal health; Propensity score analysis; Skilled Birth Attendance